ChatGPT and prompt engineering for software development. (Packt Publishing, 2023)
ChatGPT is an advanced language model that generates human-like text. Prompt engineering involves shaping prompts to elicit desired responses, a valuable technique in software development, allowing developers to interact with ChatGPT for explanations, code snippets, design suggestions, and documentation assistance. The course begins with an introduction to ChatGPT, its capabilities, and applications in software development. You will learn to use ChatGPT for certification preps as a study aid and resource to understand key concepts. The course covers how ChatGPT can be utilized for tech interview preparation, practicing coding challenges, answering technical questions, and enhancing interview performance. We will explore how ChatGPT can be used in Docker, understanding Docker concepts. Moving on, we will delve into designing software systems with ChatGPT and brainstorm and evaluate design options, patterns, and trade-offs. You will learn to program with ChatGPT, seek explanations, and code examples in various programming languages/frameworks. Upon completion, we will gain a comprehensive understanding of ChatGPT/prompt engineering techniques that will enable us to effectively utilize ChatGPT to enhance software development productivity and acquire skills to design systems, write programs, and create documents with the assistance of ChatGPT. What You Will Learn Use ChatGPT to develop software on different languages/frameworks Learn strategies for using ChatGPT to prepare for certifications Explore techniques to excel in technical interviews using ChatGPT Integrate ChatGPT with Docker for enhanced development workflows Design software systems using ChatGPT for improved design options Build software development projects with ChatGPT to boost productivity Audience This course is ideal for beginners interested in using ChatGPT for software development. Whether you are a software developer, engineer, or someone looking to enhance productivity in software development, this course is designed to equip you with the necessary skills to leverage ChatGPT effectively. Regardless of your current level of expertise, this course will help you harness the power of ChatGPT to boost your productivity and optimize your software development workflows. Basic programming knowledge is recommended as a prerequisite for this course. About The Author Praveenkumar Bouna: Praveenkumar Bouna is a highly rated cloud instructor with a 4.5 instructor rating and over 2,869 reviews. He has taught over 31,154 students across 18 courses. With a background in the security domain and experience at Honeywell, Praveen has extensive expertise in designing and developing products using the .NET stack. He holds a patent and has presented two papers in the field. Praveen is a Certified ScrumMaster (CSM) and has served as a Scrum Master for a Security R&D team for over 6 years. He has published 30+ Udemy courses and Udemy Labs, sharing his knowledge with over 25,000 students on various software development topics. Explore Praveenkumar Bouna's courses below, covering Azure, Web Development, Scrum, and C# Development, to expand your skills in these areas.